PELATIHAN ADMINISTRASI KEUANGAN KOPERASI DALAM MENDUKUNG PROGRAM KOPERASI MERAH PUTIH - Usmar, Andi; Resa Sania Kamila; Fatma azka Azkia Ma’ruf; Nunung Nurhayati; Fajar Dimas Saputra (Jurnal Pengabdian Indonesia (JPI), 2026)
Strengthening the financial administration capacity of cooperatives is a crucial element in supporting the sustainability and accountability of cooperative institutions in Indonesia. This community service activity aims to improve the understanding and skills of cooperative administrators in financial administration through a hybrid Pelatihan (online and offline). This program aligns with the government's "Red and White Cooperative" initiative, which promotes digitalization and professional cooperative governance. The Pelatihan was conducted using a participatory approach involving lecturers, students, and cooperative actors. Results showed an increase in participants' understanding of transaction recording, the preparation of simple financial reports, and the importance of transparency in cooperative fund management. Technical challenges in the hybrid implementation can be overcome with active mentoring and the use of appropriate digital platforms. This activity demonstrates that the hybrid approach can reach a wider audience and is effective in transferring knowledge